A Brief History of Poisons - Abd Razak, Dzulkifli (1995)
"Let me have, A dram of poison, such soonspeeding gear, As will disperse itself through all the veins, That the liftweary talker may fall dead, And that the trunk may be discharged of' breath, As violently as hasty powder fir'd, Doth hurry from the fatal cannon's womb." Today, poisonings are a significant cause of mortality and morbidity. A 16th century physician, Paracelsus noted that all substances known to man are poisons, and only the amount or dose determines the effect. As such, poisons have been part of the history of mankind. From the days of Socrates to the present time, poisons have never ceased to be an integral part of man. A number of wellknown literature's never failed to mention the word 'poisons' since time immemorial. The famous being William Shakespeare's Romeo and Juliet: In more recent times, Agatha Christie in her writings often used poisons as part of her plot. Since 1920 until 1975, among the 85 books that she wrote, 41 involved poisons; whereas of the 148 short stories written, poisons were implicated in 24 of them. Likewise, Lewis Carroll in her famous book 'Alice in Wonderland,' wrote: